Quality and Quality Control Procedures Histological Laboratory , Department of Pathology - Sedano Gelvet, Eduardo (1998)
This article presents , first, the importance of the Histological Laboratory , Department of Pathology Procedures ( DP ) in medical practice , then a review of the concept of quality and its relationship with the different activities within the laboratory is . In addition, some examples of misconceptions about the quality intended by many of us are given . Also highlight the complexities of obtaining a histological preparation quality . Some criteria are proposed to help members of the Histological Laboratory Procedures DP to understand the different aspects of quality are achieved with methods that perform equipment, and provide some tips on appropriate quality control and treatments are needed .